(untitled) (Minerva, 2019)
This article attempts to draw a parallel between the Greek and the Hindu myths about the constellation of the Pleiades, which are, in the Vedic and Sanskrit texts, the wives of the Seven Rishi (or Sages). Some Greek passages equating the Pleiades with Doves (’Peleiades’) are also discussed.